2013
DOI: 10.1590/s0100-69912013000500010
|View full text |Cite
|
Sign up to set email alerts
|

Complementação por coagulação com plasma de argônio após a ressecção endoscópica completa pela técnica de fatiamento para grandes adenomas colorretais

Abstract: Complementation by argon plasma coagulation after apparent complete endoscopic piecemeal resection of large sessile colorectal adenomas does not seem to reduce the occurrence of residual adenomatous lesions or local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The number of lesions included in the APC studies is very small (Brooker et al n = 21; Albuquerque et al n = 21). Furthermore, the study by Brooker et al showed a recurrence rate of 63.6 % in the control group, which raises the question whether these data are representative for current practice 18 19 . In addition to the studies by Brooker et al and Albuquerque et al, an abstract by Chattree and Rutter (2015) also reported data on the effect of APC on recurrence.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The number of lesions included in the APC studies is very small (Brooker et al n = 21; Albuquerque et al n = 21). Furthermore, the study by Brooker et al showed a recurrence rate of 63.6 % in the control group, which raises the question whether these data are representative for current practice 18 19 . In addition to the studies by Brooker et al and Albuquerque et al, an abstract by Chattree and Rutter (2015) also reported data on the effect of APC on recurrence.…”
Section: Discussionmentioning
confidence: 94%
“…Settings for APC show more variation between operators, with currents between 30–70 Watts and a gasflow of 0.8–2.0 liters per min 18 19 24 25 . A recent study in porcine models evaluating the effects of STSC and APC showed that APC applied at 1.0 L/min, 30 W, was associated with islands of preserved mucosa 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Using the inclusion/exclusion criteria, a total of 13 studies with 2686 patients were included ( Figure 1 and Table 1 ) [ 12 , 13 , 16 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Two of the studies were published as a single article [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was an important finding in EMR because there exist unseen residual neoplastic cells at the margins of the snare trajectory. Intuitively, other interventions targeting the EMR margins have also been introduced in endoscopy practice along with extended EMR 26 , such as precutting EMR 27 , APC 28 29 , and STSC 7 9 . In general, these interventions decrease recurrence rates by as much as 63 % 30 , with APC and STSC demonstrating superior efficacy in recurrence reduction compared to extended EMR and precutting EMR as per subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%